I am after to model the Doppler shift of an LEO satellite. At [1] (pp 183) I have found the following formula:


$f_s$ stable frequency transmitted from the satellite

$f_r$ received (Doppler shifted) frequency at the observation point.

$u$ satellite velocity

$c$ velocity of light

$\theta$ angle between the velocity vector of the satellite and the observer-satellite line of sight

After some further research, I see that falls in one of the theories of estimating the Doppler effect.

Can I please ask how to derive the nominator of the above formula? I have found several references but am not yet convinced.

[1]Seeber, G. (2003). Satellite Geodesy.New York, Walter de Gruyter


2 Answers 2


In the following replace $\:^{\prime}$$^{\prime}$Star$\:^{\prime}$$^{\prime}$ by $\:^{\prime}$$^{\prime}$satellite$\:^{\prime}$$^{\prime}$.

Solution 1 enter image description here

Suppose two light pulses $p'_1$ and $p'_2$ are emitted successively from the Star towards the Earth at time moments $t'_1$ and $t'_2$, apart by an infinitesimal time interval $\mathrm{d}t'=t'_2\!-\!t'_1$. Time $t'$ is the time in the rest frame $\mathrm{S'}$ of the Star.

These two events happen in the rest frame $\mathrm{S}$ of the Earth at time moments $t_1$ and $t_2$, apart by the dilated infinitesimal time interval $\mathrm{d}t=t_2\!-\!t_1=\gamma\left(v\right)\mathrm{d}t'$. Time $t$ is the time in the rest frame $\mathrm{S}$ of the Earth.

Now, let the two light pulses arrive to Earth at Earth time moments $\hat{t}_{\!1}$ and $\hat{t}_{\!2}$, apart by an infinitesimal time interval $\mathrm{d}\hat{t}=\hat{t}_{\!2}\!-\!\hat{t}_{\!1}$. If the Star would be at rest relatively to Earth or its motion would be transverse (no radial motion : $v_\mathrm{r}=0$) then $\mathrm{d}\hat{t}=\mathrm{d}t$. But because of the radial motion of the Star relatively to Earth the 2nd pulse, which emitted later, has to run a larger distance than the 1rst pulse if the Star is moving away or has to run a smaller distance than the 1rst pulse if the Star is approaching. In the first case $\mathrm{d}\hat{t}>\mathrm{d}t$. In the second case, that shown in the Figure, $\mathrm{d}\hat{t}<\mathrm{d}t$.

So, if we could estimate the time interval $\mathrm{d}\hat{t}$ then we would solve the problem since the time intervals are inversely proportional to frequencies that is proportional to wavelengths : \begin{equation} \dfrac{\mathrm{d}\hat{t}}{\mathrm{d}t'}=\dfrac{\nu'}{\nu}=\dfrac{\lambda}{\lambda'}=\dfrac{\lambda \text{(observed)}}{\lambda'\text{(emitted)}} \tag{01} \end{equation}

enter image description here

As shown in Figure-02 above

\begin{equation} \mathrm{d}t=t_2\!-\!t_1=\gamma(v)\left(t'_{\!2}\!-\!t'_{\!1}\right) =\gamma(v)\mathrm{d}t' \tag{A} \end{equation}

\begin{equation} \mathrm{dr}\approx \mathrm{r_2}-\mathrm{r_1}=-v_\mathrm{r}\,\mathrm{d}t=-v \cos\theta\, \gamma(v)\,\mathrm{d}t' \tag{B} \end{equation}

\begin{equation} \mathrm{d}\hat{t}=\hat{t}_2\!-\!\hat{t}_1=\left(t_2\!+\!\dfrac{ \mathrm{r}_2}{c}\right)\!-\!\left( t_1\!+\!\dfrac{ \mathrm{r}_1}{c} \right)=\mathrm{d}t\!+\!\dfrac{\mathrm{dr}}{c} =\gamma(v)\mathrm{d}t'\!-\!\dfrac{v \cos\theta\, \gamma(v)\,\mathrm{d}t' }{c} \Longrightarrow \nonumber \end{equation}

\begin{equation} \dfrac{\mathrm{d}\hat{t}}{\mathrm{d}t' } = \dfrac{1\!-\!\dfrac{v \cos\theta}{c}}{ \sqrt{1\!-\!\dfrac{v^2}{c^2}}} \stackrel{\left(\beta=\tfrac{v}{c}\right)}{=\!=\!=}\dfrac{1\!-\!\beta \cos\theta}{\sqrt{1\!-\!\beta^2}}=\dfrac{\nu' \text{(emitted)}}{\nu\:\text{(observed)}} =\dfrac{\lambda\:\text{(observed)}}{\lambda' \text{(emitted)}} \tag{C} \end{equation} QED.


Solution 2

Link : My answer in About de Broglie relations

For a plane wave the angular frequency 4-vector \begin{equation} \boldsymbol{\Omega} \equiv \left(\omega,c\mathbf{k} \right) \tag{2.01} \end{equation} is transformed between frames under the Lorentz transformation. This is proved in the link for a more general configuration of two frames (see the Figure in the end of the link). In (2.01) \begin{equation} \omega= 2\pi\nu \tag{2.02} \end{equation} is the angular frequency and $\:\nu\:$ the frequency. Also \begin{equation} \mathbf{k}= \dfrac{ 2\pi}{\lambda} \;\mathbf{m} , \qquad \Vert \mathbf{m}\Vert =1 \tag{2.03} \end{equation} is the wave 3-vector and $\:\lambda\:$ the wavelength. The plane wave $^\prime$$^\prime$propagates$^\prime$$^\prime$ with velocity vector \begin{equation} \mathbf{w}= \dfrac{ \omega}{\Vert \mathbf{k}\Vert } \;\mathbf{m}=\lambda\nu\;\mathbf{m} = \dfrac{ \omega}{\Vert \mathbf{k}\Vert^{2}}\mathbf{k}, \qquad \Vert \mathbf{w}\Vert \equiv \mathrm{w} = \dfrac{ \omega}{\Vert \mathbf{k}\Vert }=\lambda\nu \tag{2.04} \end{equation} From the Lorentz equation (A-14b) in the link we have \begin{equation} \omega^{\boldsymbol{\prime}} =\gamma\left(\omega\!+\!\dfrac{ \mathbf{v}\boldsymbol{\cdot}c\mathbf{k}}{c}\right) \tag{2.05} \end{equation} For a light wave $\: \mathbf{k}=(2\pi\nu/c)\mathbf{m}\:$ so \begin{equation} \nu^{\boldsymbol{\prime}} =\gamma\left(1\!+\!\dfrac{ \mathbf{v}\boldsymbol{\cdot}\mathbf{m}}{c}\right)\nu \tag{2.06} \end{equation} In above equation $\:\mathbf{v}=\!-\boldsymbol{v}\:$ is the velocity vector of the Earth relatively to the Star , the vector $\:\boldsymbol{v}\:$ shown in Figures-01,-02 and $\:\mathbf{m}\:$ the unit vector parallel to its radial component $\:\boldsymbol{v}_{\mathrm{r}}\:$ \begin{equation} \mathbf{m}=\dfrac{\boldsymbol{v}_{\mathrm{r}}}{\Vert\boldsymbol{v}_{\mathrm{r}}\Vert} \tag{2.07} \end{equation} so that finally \begin{equation} \dfrac{\nu' \text{(emitted)}}{\nu\:\text{(observed)}}=\gamma\left(1\!-\!\dfrac{ v \cos \theta}{c}\right)= \dfrac{1\!-\!\dfrac{v \cos\theta}{c}}{ \sqrt{1\!-\!\dfrac{v^2}{c^2}}} \tag{2.08} \end{equation}


Strangely enough, it does not seem the transverse Doppler effect has been demonstrated on Physics SE. This is a trivial consequence of the Lorentz transformation of 4-wave vector. Denoting by $\omega$ the pulsation and by $(k_x, k_y, k_z)$ the wave-vector, $(\omega, k_x, k_y, k_z)$ is a 4-vector and therefore the transformation between the frame $S$ where the satellite is at rest and the frame $R$ where the receiver is at rest is

$$\begin{align} \omega_R &= \gamma(\omega_S + u\,k_{S,x})\\ k_{R,x} &= \gamma(k_{S,x} + u\, \omega_S)\\ k_{R,y}&=k_{S,y}\\ k_{R,z}&=k_{S,z}\\ \gamma&=(1-u^2)^{-\frac{1}{2}}\\ \end{align} $$

where the $x$-axis is oriented along the speed of $S$ wrt to $R$. I wrote all of them but we are going to use the first one only. Oh, and I used units where c=1. The next step is to use the relation between the pulsation and the length of the wave vector and introduce an angle for the direction of propagation

$$k_{S,x} = \omega_S\cos\phi,$$

where $\phi$ is the angle between the wave vector and the direction $\overrightarrow{SR}$. Then


This is your formula since $\phi = \pi - \theta$ as you consider the angle between $\overrightarrow{RS}$ and the wave vector instead. After re-introducing $c$ of course…

A great reference for undergraduate on that and much more is the classic

Wolfgang Rindler, Introduction to Special Relativity, 2nd ed. Oxford University Press, 1991.

  • $\begingroup$ Thanks very much for your reply,Is it possible to point me on some references for background reading on that? $\endgroup$
    – Rizias
    Jun 13, 2017 at 14:32

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.